Usaha Pembaharuan Abdullah Ahman - Fachri Syamsuddin (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2013)
After the completion of his study in the Middle East, Abdullah Ahmad – upon his arrival in Minangkabau – started to establish an educational institution, Sekolah Adabiah, the first ever classical school system to have been founded by Minangkabau moslem. Abdullah Ahmad then established Syarikat Oesaha Adabiah, the foundation which managed the school. In order to spread his reform ideas, he published a periodical called al-Munir. In addition, Abdullah Ahmad also founded an organization for religious teachers, PGAI (Persatuan Gugu-guru Agama Islam).